Impact of Human Imposed Pressure on Pheasants of Western Himalayas, Pakistan: Implication for Monitoring and Conservation - Muhammad Azhar Jameel (17542020) (2022)
Pheasants play a distinctive and significant role in high altitudinal ecosystems. These are good indicators of environmental changes, and their presence determines the health and balance of the bio-network. Recent human pressure continues to degrade their populations, and some pheasant species are already extinct. Therefore, the current study focuses on pheasant abundance and emerging conservation issues. The pheasant population was assessed using “Call count methods” and analyzed by DISTANCE software. The results revealed that the valleys where human interference is minimum had significantly higher encounter rates and densities of pheasants. At the same time, the pheasant population was severely affected, whether found at lower or higher altitudes, showing seasonal migration toward human settlements. The habitat suitability modeling was performed using the MaxEnt model and showed that human activities overlap with the suitable natural habitats of pheasants. The threats were identified using a systematic questionnaire survey from the nearest villages of the potential habitat, and particular attention was paid to valleys where human pressures were found to be high. Major infrastructure development projects, illegal hunting, and deforestation were identified as the major threats to the pheasant population. The study concluded that proper conservation measures are required to protect pheasants in their potential habitats. Other Information Published in: Diversity License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/d14090752 Disclaimer: The University of Doha for Science and Technology replaced the now-former College of the North Atlantic-Qatar after an Amiri decision in 2022. UDST has become and first national applied University in Qatar; it is also second national University in the country.